Smart City Masterplan Policy Innovation In Public Service Development In The City Of Padang Panjang (Sustainability (STPP) Theory, Practice and Policy, 2023)
Smart City is a city management that utilizes various resources effectively and efficiently to solve various city problems using innovative, integrated and sustainable solutions to provide infrastructure and provide city services that can improve the quality of life of its citizens. The digital transformation process carried out in the City of Padang Panjang and all efforts to increase digitization and increase digital literacy. Based on the relatively fast population, it can cause various problems typical of urban areas, such as a decrease in the quality of public services, reduced availability of residential land, congestion on the highway, difficulty in getting a parking space, accumulation of garbage, and other social problems. In this study the approach used is a qualitative approach, used to examine the condition of natural objects, where the researcher is the key instrument, the data collection technique is done by triangulation (combined). After doing the research, it can be seen that the purpose of the smart city program in the city of Padang Panjang is where the community can participate in helping the management of existing resources and participate in providing the right information to the local community. The goal is to provide innovative solutions in handling and solving major problems, providing convenience, security and comfort for the community, improving the quality of life of the people of Padang Panjang City to a better level.